SCREENING OF DROUGHT TOLERANT LEVEL OF SOME WHEAT CULTIVARS (Triticum Durum Desf.) UNDER WATER STRESS - levent yorulmaz; sibel ipekesen; muhammet oner; cuma akinci; Behiye Tuba Bicer (Journal of Animal and Plant Sciences, 2025)
Wheat is an important agricultural crop in Turkey's agricultural production system; however, recently drought stress is one of the most important reasons for the decrease in yields in wheat production regions of Turkey. Therefore, it is important to identify genotypes or cultivars that are less affected by drought stress. The aim of this study was to determine the performance of ten wheat genotypes against water stress. Water stress was applied from seed emergence to seed maturity accounting for 100% and 50% field capacity. Nine agro-morphologic traits were evaluated under semi-controlled greenhouse conditions. The experiment was arranged in Randomized Complete Block design with four replications.Data analysis were realized parameters such as the heading time, plant height, spike length, the number of fertile spikelet/plant, the number of grains per spike, grain weight per plant, SPAD values at heading (51.06) and flowering stages and protein ratio. Water stress reduced heading time (66.45 days), plant height (36.36 cm), spike length (3.72 cm), the number of fertile spikelet/plant (9.99), the number of grains per spike (5.82), grain weight per plant (0.25 g). SPAD values at heading (51.06) and flowering stages (52.44) and protein ratio (23.07%) was increased under water-stressed conditions. Anzele genotype was the highest tolerant to water stress for grain number spike-1 (11.13) and grain weight plant-1 (0.48 g). Burgos genotype had the best performance for protein ratio (27.47%) under water stressed conditions. The variations among cultivars for examined traits indicated that Anzele and Burgos cultivars could be considered for breeding programs in future.
Keywords: Triticum durum; water stress; field capacity; grain weight